Kecernaan dan Fermentabilitas Tandan Kosong Sawit yang di Fermentasi dengan Mikroba Tanah secara in- vitro - Mardiati Zain (Universitas Andalas, 2006)
The objective of this research was to determine the effect of fermentation by soil microbes on the in vitro DM, NDF, ADF digestibility and fermentability characteristics of palm empty bunch. Palm empty bunch is fermented by 10% soil microbes inoculum / kg DM with length of 0, 1, 2 and 3 weeks fermentation at aerobic condition. Digestibility was determined after 48 h incubation with rumen fluid of Tilley and Terry technique. Data were analyzed as a Block randomized Design. Digestibility of DM, NDF and ADF, were difference among treatments. In vitro DM digestibility after 48 h was higher for 2 weeks of fermentation (50,36%) than for 0, 1, and 3 week fermentation (33,72, 48,09, and 46,36 %) (P<0,05). Neutral Detergen Fiber digestibility after 48 h was higher for 2 weeks of fermentation (39,5 %) than for 0, 1, and 3 wk fermentation ( 28,8, 34,82, and 30,56 %) (P<0,05). In vitro ADF digestibility after 48 h was also higher for 2 weeks of fermentation (34.88 %) than for 0, 1, and 3 wk fermentation (20,9, 29,73, and 26.) (p<0.05). The average of pH was non difference among treatment. Concentration of NH3 was increase for all treatment, and concentration of VFA was also higher for 2 weeks fermentation (113,46 mM). It was concluded that palm empty bunch fermented by soil microbes for length of 2 weeks fermentation has better digestibility and fermentabitity.